Brexit : Eurosceptic Victory In British Referendum In Term Of Britain Membership Of European Union - Khairul Munzilin; Ali Muhammad (Universitas Muhammadiyah Ponorogo, 2017)
On June 23, 2016, eurosceptic group won a British referendum on Britain's motion of leaving the European Union. This paper will explore the factors related to the victory of eurosceptic group in the historic referendum. This paper uses theory of voting behaviour and strategy of campaign to answer the research of this paper. Eurosceptic group victory in this referendum couldn’t be separated from eurosceptic's success in influencing the mindset of Britishsociety as the voter in this referendum. By using the concept of the campaign strategy, the writer will examine various forms of brexit campaign strategy that used to influence voters behaviour.